Information coverage of the foreign policies of Belarus, Russia, Ukraine in the second half of the 2010s: new resources and instruments - Froltsov, Vladislav V. (Journal of the Belarusian State University. International Relations, 2019)
The article considers the main resources and instruments for information coverage of the foreign policies of the Republic of Belarus, the Russian Federation and Ukraine. They are used in the second half of the 2010s to promote national interests in the context of the active development of information and communication technologies and their more increasing use for the implementation of foreign policy tasks. The relevant approaches to realization of the digital diplomacy are identified and characterized, including an expansion of presence in the leading social networks, key features of broadcasting organization of the international satellite TV channels and use of the anonymous political Telegram channels for working with foreign audiences.